1979
DOI: 10.3758/bf03213827
|View full text |Cite
|
Sign up to set email alerts
|

The tilt illusion: Length and luminance changes of induction line and third (disinhibiting) line

Abstract: Direct effects (acute-angle expansion) and indirect effects (acute angle contraction) aspects of the tilt illusion were reduced by reductions in the length as well as the luminance of the induction line, and also by the addition of a third line to the display. When this third (disinhibiting) line was also reduced in length and luminance, the reduction in the illusion became less and the illusion increased in magnitude. The illusion size was also changed by increasing the orientation difference between the disi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1979
1979
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…The current results, which suggest that M1 orientations of greater than 15 deg cannot disinhibit equal energy M2s of lesser orientations, are in partial agreement with those of Wenderoth and Tyler (1979), who reported that, in a simultaneous masking paradigm, a O-deg (i.e., vertical) grating could also be disinhibited by orientations of 75 and 90 deg (i.e., approximately horizontal). With the exception of these latter results, the orientation over which disinhibition resulted is extremely similar to the orientation tuning ranges isolated by other psychophysical techniques (Campbell & Maffei, 1970;Fidell, 1972;Gilinsky & Mayo, 1971;O'Toole, 1979;Over et al, 1972). The present data support the suggestion that disinhibition may arise by lateral inhibition in populations of feature detecting neurons.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The current results, which suggest that M1 orientations of greater than 15 deg cannot disinhibit equal energy M2s of lesser orientations, are in partial agreement with those of Wenderoth and Tyler (1979), who reported that, in a simultaneous masking paradigm, a O-deg (i.e., vertical) grating could also be disinhibited by orientations of 75 and 90 deg (i.e., approximately horizontal). With the exception of these latter results, the orientation over which disinhibition resulted is extremely similar to the orientation tuning ranges isolated by other psychophysical techniques (Campbell & Maffei, 1970;Fidell, 1972;Gilinsky & Mayo, 1971;O'Toole, 1979;Over et al, 1972). The present data support the suggestion that disinhibition may arise by lateral inhibition in populations of feature detecting neurons.…”
Section: Resultssupporting
confidence: 88%
“…Also, interchannel inhibition may modify a neuron's response, but only to the extent that the channels are responsive to the same or overlapping spatial dimensions in the stimuli. This latter explanation has been offered to account for the occurrence of disinhibition in orientation illusion (Blakemore, Carpenter, & Georgeson, 1970;O'Toole, 1979), aftereffect (Magnussen & Kurtenbach, 1980), and masking (Wenderoth & Tyler, 1979). Barry and Dick (1972) and Purcell and Dember (1968) have suggested that disinhibition in Robinson's (1966) paradigm may arise as successive brightness contrast or brightness reversal.…”
Section: N R Long and J G M Scheirlinckmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary aim of this experiment was to provide a further test of the hypothesis that the simple and complex versions of the Fraser illusion reflect the operation of the same visual information processes in relation to orientation. One of the most important features of the illusions that are thought to result from orientation-specific inhibition is their dependence on luminance contrast (Davidoff, 1973;O'Toole, 1979;Oyama, 1975;Parker, 1974;Stuart & Day, 1980;Wallace, 1975). Wallace (1975), who showed that the strength of the Zollner illusion was a function of the log contrast of the lines making up the illusion, related this to the increase in the firing rate of cortical cells that accompanied increases in luminance contrast.…”
Section: Resultsmentioning
confidence: 99%
“…The “indirect” effect occurs when the acute angle is relatively large (>50°) (Gibson & Radner, 1937; O'Toole, 1979; O'Toole & Wenderoth, 1977; Wenderoth & Johnstone, 1988) (Figure 8). Kitaoka and Ishihara (2000) revealed that this illusion can occur even when the angle is smaller than 45°, if the induced line is single and the inducing lines are long enough.…”
Section: Fraser Illusionmentioning
confidence: 99%